Genetic evidence for widespread population size expansion in North American boreal birds prior to the Last Glacial Maximum. Issue 1991 (25th January 2023) - Kimmitt, Abigail A.; Pegan, Teresa M.; Jones, Andrew W.; Wacker, Kristen S.; Brennan, Courtney L.; Hudon, Jocelyn; Kirchman, Jeremy J.; Ruegg, Kristen; Benz, Brett W.; Herman, Rachael; Winger, Benjamin M.
Abstract : Pleistocene climate cycles are well documented to have shaped contemporary species distributions and genetic diversity. Northward range expansions in response to deglaciation following the Last Glacial Maximum (LGM; approximately 21 000 years ago) are surmised to have led to population size expansions in terrestrial taxa and changes in seasonal migratory behaviour. Recent findings, however, suggest that some northern temperate populations may have been more stable than expected through the LGM. We modelled the demographic history of 19 co-distributed boreal-breeding North American bird species from full mitochondrial gene sets and species-specific molecular rates. We used these demographic reconstructions to test how species with different migratory strategies were affected by glacial cycles. Our results suggest that effective population sizes increased in response to Pleistocene deglaciation earlier than the LGM, whereas genetic diversity was maintained throughout the LGM despite shifts in geographical range. We conclude that glacial cycles prior to the LGM have most strongly shaped contemporary genetic diversity in these species. We did not find a relationship between historic population dynamics and migratory strategy, contributing to growing evidence that major switches in migratory strategy during the LGM are unnecessary to explain contemporary migratory patterns.